2013
DOI: 10.1038/jid.2013.149
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cardiovascular Disease in Individuals with Psoriasis: A Systematic Review and Meta-Analysis

Abstract: The relationship between psoriasis and increased risk of cardiovascular disease (CVD) is controversial. We critically evaluate 14 cohorts and meta-analyze the magnitude of CVD risk for the primary outcomes of CVD mortality, stroke, and myocardial infarction (MI), and establish subgroup risk for different psoriasis severities and age groups. Increased CVD risk was identified only in individuals with severe psoriasis (defined as requiring systemic therapy or hospital admission): the risk ratio relative to the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
199
0
11

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(226 citation statements)
references
References 34 publications
5
199
0
11
Order By: Relevance
“…Bulgular: Psoriazisli hasta (n=43) ve kontrol grubu (n=47) arasında vücut kitle indeksi, alkol tüketimi ve kahve tüketimi açısından anlamlı farklılık yoktu. Medyan PAŞİ 10,0 (8,[3][4][5][6][7][8][9][10][11][12]8) idi. Sigara kullanan kişi oranı psoriazisli hastalarda anlamlı yüksekti.…”
Section: öZunclassified
See 1 more Smart Citation
“…Bulgular: Psoriazisli hasta (n=43) ve kontrol grubu (n=47) arasında vücut kitle indeksi, alkol tüketimi ve kahve tüketimi açısından anlamlı farklılık yoktu. Medyan PAŞİ 10,0 (8,[3][4][5][6][7][8][9][10][11][12]8) idi. Sigara kullanan kişi oranı psoriazisli hastalarda anlamlı yüksekti.…”
Section: öZunclassified
“…It is characterized by hyperproliferation and poor differentiation of epidermal keratinocytes. Many studies conducted in recent years have shown that psoriatic patients, especially those with severe psoriasis, have increased risk of cardiovascular disease (CVD) and mortality associated with CVD [1][2][3] . The usual CVD risk factors, such as metabolic syndrome, smoking, and alcohol consumption that often accompany psoriasis, the lipid-(cyclosporin and acitretin) and homocysteineelevating (methotrexate) effects of the drugs used for treating psoriasis, and inflammation in the pathogenesis of psoriasis that show apparent parallelism with atherosclerosis are thought to contribute to this predisposition 4,5 .…”
Section: Introductionmentioning
confidence: 99%
“…The release of inflammatory mediators by keratinocytes has several effects: the attraction of additional immune cells (e.g. macrophages, and neutrophils), the production of collagen and proteoglycans by fibroblasts, the activation and perpetuation of an inflammatory response, and the propagation of an adaptive immune response (11,65). Hence, the outcomes of stimulation of a small region of psoriasis-predisposed skin results in an immune reaction that can lead to the development of lesions at local and distant body sites, as well as systemic effects.…”
Section: Plaque Development and The Immune Response In Psoriasismentioning
confidence: 99%
“…Psoriasis has also been reported to be associated with metabolic disorders including obesity, non-alcoholic fatty liver disease (NAFLD), dyslipidaemia, and diabetes, as well as disorders that confer an unfavorable cardiovascular risk profile and higher mortality rates. These risks may be directly related to disease severity and duration, although the strength of the association varies across studies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Recent research suggests that patients with psoriasis have a systemic inflammatory state, putting them at increased risk of cardiovascular complications, including metabolic syndrome, peripheral vascular disease, stroke, myocardial infarction, and cardiac death. 3,4 Some articles suggest that tumor necrosis factor inhibitors may decrease the risk of stroke and myocardial infarction in patients with psoriasis. 5,6 As understanding of the disease has continued to evolve over five decades, research interests have expanded.…”
Section: Introductionmentioning
confidence: 99%